2020
DOI: 10.1111/epi.16544
|View full text |Cite
|
Sign up to set email alerts
|

Severe psychological distress among patients with epilepsy during the COVID‐19 outbreak in southwest China

Abstract: Objective:To compare the severity of psychological distress between patients with epilepsy and healthy controls during the COVID-19 outbreak in southwest China, as well as identify potential risk factors of severe psychological distress among patients with epilepsy. Methods: This cross-sectional case-control study examined a consecutive sample of patients older than 15 years treated at the epilepsy center of West China Hospital between February 1 and February 29, 2020. As controls, sex-and age-matched healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 41 publications
5
128
2
5
Order By: Relevance
“…This suggests that PWE are at higher risk of mental diseases. Hao and colleagues reported that patients with drug-resistant epilepsy and the heighted media exposure were significantly related to increases in psychological stress [11]. In our study, we observed no significant relation of increase in self-reported stress to the number of AEDs and baseline seizure frequencies.…”
Section: Discussioncontrasting
confidence: 78%
“…This suggests that PWE are at higher risk of mental diseases. Hao and colleagues reported that patients with drug-resistant epilepsy and the heighted media exposure were significantly related to increases in psychological stress [11]. In our study, we observed no significant relation of increase in self-reported stress to the number of AEDs and baseline seizure frequencies.…”
Section: Discussioncontrasting
confidence: 78%
“…Severe psychological distress has recently been reported to be more common among 252 epilepsy patients during the COVID-19 outbreak in southwest China when compared to normal subjects. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggested that the anxiety level of people with epilepsy is not significantly higher than the general population without epilepsy. A recent study that assessed the anxiety level in people with epilepsy reported significantly higher anxiety level among patients in contrast to the general population [10]. This discrepancy in findings may be related to background situation of COVID-19 pandemic in the regions where the studies were conducted, facilities in the national healthcare systems provided to people with epilepsy, or a higher anxiety level among the general population.…”
Section: Discussionmentioning
confidence: 88%